Health education for mothers with hospitalized newborns: experience report (Research, Society and Development, 2021)
The study aims to describe the educational actions carried out with mothers of hospitalized premature children. It is an experience report, with a qualitative approach, developed by nursing students, from workshops held in a support house called Casa da Mamãe, linked to a teaching hospital in the north of Ceará. The meetings were held from May to July 2019 and took place weekly. To collect the information, the field diary was used, and later, the records were analyzed together with the literature. Nine meetings were held with the puerperal women, and the following themes were worked on through the following educational workshops and active methodologies: taking care of the caregiver, caring for the newborn, promoting and sharing feelings, among other actions done through dynamics, massages, paintings and art therapy. The activities carried out with the group of puerperal women provided learning moments for all those involved, reaffirming the idea that health promotion actions should be eminently participatory and transformative. The nursing academic team helped to favor the bond, through health education activities, moments of relaxation and self-knowledge, in addition to strengthening the relationship of mutual support between mothers.